Naphthoxazoles Derived from Lapachol as Fluorescent DNA Probes: Synthesis and Binding Studies with Calf Thymus DNA - Guimarães, Délis G.; Santos, Victória L.A.; Simplicio, Sidney S.; Gonsalves, Arlan A.; Gouveia, João J.S.; Almeida, Fernanda B. [UNESP]; Gusmão, Luiza A.; Tedesco, Antonio C.; Primo, Fernando L. [UNESP]; Rolim, Larissa A.; Araújo, Cleônia R.M. (Sociedade Brasileira de Quimica (SBQ), 2025)
This study evaluated the potential of naphthoxazoles derived from lapachol as fluorescent deoxyribonucleic acid (DNA) probes. We synthesized three 2-substituted naphthoxazoles: one with a phenyl group (LOX1), and two with 2-hydroxyphenyl (LOX2) and 4-fluorophenyl (LOX3) groups, respectively. The compounds were synthesized using the Debus-Radziszewski reaction between the lapachol and aldehydes. The quantum yield (Φf) was determined using the classical relative method with 4’,6-diamidino-2-phenylindole (DAPI) as the standard, and the fluorescence lifetime (τf) was measured with a lifetime fluorescence spectrometer. The naphthoxazoles exhibited low fluorescence emission and consequently low values of Φf in their free form, demonstrating behavior similar to that of DAPI. These compounds displayed notably large Stokes shifts (approximately 340 nm) and the τf in the nanosecond range. DNA binding studies were conducted by monitoring changes in the absorption properties of naphthoxazoles in the absence and presence of calf thymus DNA at different concentrations. The results indicated that naphthoxazoles interacted with DNA through groove binding. LOX2 exhibited a binding constant (Kb) of 2.70 × 104 M-1, indicating strong binding to the biomolecule. These findings underscore the potential of LOX1, LOX2, and LOX3 as candidates for use as fluorescent DNA probes.
Keywords: DNA dye; fluorescent marker; groove binder; natural naphthoquinone; oxazole